Long-term Double-J stenting is superior to short-term Single-J stenting in kidney transplantation. - Christiaan A J Oudmaijer; Kelly Muller; Erika van Straalen; Robert C Minnee; Diederik J A N Kimenai; Marlies E J Reinders; Jacqueline van de Wetering; Jan N M IJzermans; Turkan Terkivatan (PLoS ONE)
Background and objectives Urological complications after kidney transplantation, due to the ureteroneocystostomy, are associated with significant morbidity, prolonged hospital stay and even mortality. Ureteral stents can minimize the number of complications but are not consistently used, as previous studies were retrospective in nature. We aim to prospectively determine the most effective stenting approach. Methods We performed a non-blinded single-centre randomised controlled trial in an academic hospital. Kidney transplant recipients were randomised to either a Single-J stent or a Double-J stent, removed according to respective protocols. Primary outcome was PCN placement within six months. Secondary outcomes encompassed urinary tract infections, cost-effectiveness, and hospital admission time. The study was conducted from November 2018 to August 2023, during which 300 recipients were included with complete follow-up. Results PCN was performed in 14.5% in the Single-J group (21/145) and 4.5% in the Double-J group (7/155), p = 0.003. Multivariable logistic regression, corrected for recipient age, BMI, sex, and donor type, showed an OR of 0.26 [0.10, 0.61] (OR [95%CI]). To prevent PCN in one recipient, 10 would have to receive the Double-J. All secondary outcomes were comparable, whereas hospital admission time and cost-effectiveness analysis heavily favoured Double-J stenting. An important limitation was that Single-J participants were unable to leave, even if their recovery allowed earlier discharge. Conclusion This trial showed that Double-J stenting consistently reduced urological complications from 14.5% to 4.5%, while being highly cost-effective. Transplant surgeons should favour Double-J stenting to minimise the risk of complications.